Global Rangelands Standard: A Framework for Sustainable Pastoral Futures - Jones, Una (International Livestock Research Institute, 2024)
A presentation on the global rangelands standard and Rangelands Stewardship Council made at a Fashion for Land side event, UNCCD COP, Riyadh, 4th December 2024.